The Multinational Wage Premium and Wage Dynamics - Gianluca Orefice; Nicholas Sly; Farid Toubal (Center for Economic Studies and ifo Institute (CESifo), 2015)
Using detailed administrative data linking French firms and workers over the years 2002-2007, we document a distinct U-shaped pattern in worker-level wages surrounding the time their employer is acquired by a foreign firm, with a dip in earnings observed for several years before domestic firms switch to MNE status. This pre-acquisition decline in earnings can partly explain why prior evidence found no impact of foreign ownership on worker-level wages. Accounting for the pre-acquisition earnings dip and other confounding wage dynamics we find that MNEs increase remuneration to workers by 4.8% initially, and by 6%-8% after several years. Unique information about in-kind payments reveals that bonuses and other non-monetary remuneration also exhibit a U-shaped pattern surrounding foreign acquisition.
Keywords: F66; F14; F23; 330; multinational enterprises; wage premium; in-kind payments